2008
DOI: 10.1118/1.3005974
|View full text |Cite
|
Sign up to set email alerts
|

A genetic algorithm for variable selection in logistic regression analysis of radiotherapy treatment outcomes

Abstract: A given outcome of radiotherapy treatment can be modeled by analyzing its correlation with a combination of dosimetric, physiological, biological, and clinical factors, through a logistic regression fit of a large patient population. The quality of the fit is measured by the combination of the predictive power of this particular set of factors and the statistical significance of the individual factors in the model. We developed a genetic algorithm ͑GA͒, in which a small sample of all the possible combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…A better method is to account for the nondosimetric factors in the model itself. This has been done either by including both dosimetric and nondosimetric variables in a logistic regression model, 16,18 or by the use of a "dose modifying factor." 17,41 With the dose modifying approach, nondosimetric factors are included in, e.g., the LKB model by adjusting the effective T D 50 for different subgroups.…”
Section: B the Importance Of Including Patient-specific Factors Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A better method is to account for the nondosimetric factors in the model itself. This has been done either by including both dosimetric and nondosimetric variables in a logistic regression model, 16,18 or by the use of a "dose modifying factor." 17,41 With the dose modifying approach, nondosimetric factors are included in, e.g., the LKB model by adjusting the effective T D 50 for different subgroups.…”
Section: B the Importance Of Including Patient-specific Factors Inmentioning
confidence: 99%
“…However, many studies have demonstrated the importance of considering nondosimetric factors such as health status, surgery, chemotherapy, comorbidities, base-line organ function, and smoking status. [11][12][13][14][15][16][17][18][19][20] When fitting NTCP models with the dose distribution as the only risk factor, any other parameters influencing the outcome of the treatment act as confounding factors. This means that the best fit parameters intrinsically incorporate averages over confounding factors, which results in shallower dose-response curves.…”
Section: Introductionmentioning
confidence: 99%
“…GAs have been successfully applied to solve optimization problems, both for continuous (whether differentiable or not) and discrete functions. Variable selection for logistic regression model can be regarded as an optimization problem, and thus can be solved by GAs (7)(8)(9)(10). This article aims to provide a tutorial on how to implement GAs for variable selection.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of radiotherapy treatment-related toxicity has been of significant interest. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Toxicity prediction involves relating the dosimetric factors to the toxicity in question in a model, potentially in combination with clinical information. For urinary symptoms, the availability of such models is limited compared to rectal symptoms following prostate radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…12 In most instances, the studies suggest that the more contemporary strategies show promising results and perform better. Nevertheless, except for the series of studies on radiotherapy-induced pneumonitis, [7][8][9][10]13 the statistical-learning strategies were rarely extensively compared side-by-side. Furthermore, comparisons in the context of toxicity prediction were mostly performed using only one endpoint, probably chosen based on the clinical relevance.…”
Section: Introductionmentioning
confidence: 99%